Surface detail rendering using leap textures - Wang, Xin; Tong, Xin; Lin, Steve; Guo, Baining (2006)
The present surface detail rendering technique provides an efficient technique for applying a mesostructure to a macrostructure for an object that minimizes the amount of memory required for pre-computed data. A leap texture is pre-computed for a mesostructure by classifying each voxel in the mesostructure geometry and assigning a value in the leap texture based upon the classification. The value in the leap texture represents a distance to jump along a ray cast in any view direction when a model is decorated with the mesostructure geometry.
US Patent 7586494 B2